Effect of Helicobacter pylori eradication and high-density lipoprotein on the risk of de novo gastric cancer development - Nam, Su Youn; Park, Bum Joon; Nam, Ji Hyung; Kook, Myeong-Cherl (Gastrointestinal endoscopy, 2019)
The effect of Helicobacter pylori eradication on de novo gastric cancer is controversial, although meta-analyses suggest a reduction in gastric cancer after eradication. The effect of high-density lipoprotein (HDL) on gastric cancer has been rarely reported. In this large retrospective cohort study, participants underwent endoscopy and H pylori testing from 2003 to 2011 and underwent follow-up endoscopy and H pylori testing until 2013. H pylori infection was detected using a rapid urease test or histologic test. The H pylori eradication group was defined as successful eradication, whereas the H pylori persistent group was defined as noneradication or eradication failure. The risk of cancer was measured with hazard ratios (HRs) and 95% confidence intervals (CIs). Among 10,328 healthy subjects (5951 men; mean age, 48.7 years), 31 gastric cancers were detected during a median follow-up of 5.5 years. De novo gastric cancer developed in 21 of 3508 subjects (.6%) in the noneradication group, 4 of 2050 subjects (.2%) in the successful eradication group, and 6 of 4770 participants (.13%) in the absence of H pylori group. In the adjusted analysis, H pylori eradication decreased de novo gastric cancer risk (HR, .29; 95% CI, .10-.86) compared with the persistent group. The risk of de novo gastric cancer in absence of H pylori was also much lower compared with the persistent group (HR, .24; 95% CI, .09-.60). Low serum HDL increased the risk of de novo gastric cancer (HR, 2.67; 95% CI, 1.14-6.16). Successful H pylori eradication reduced de novo gastric cancer, whereas low HDL increased its risk. [Display omitted]